The ROS: Kinetic Kame for Humanoid Robot BarelangFC - Susanto Susanto; Junito Suroto; Riska Analia (Politeknik Negeri Batam, 2021)
A collaborative robot such as humanoid robot which able to play soccer consist tons of software framework such as servo controller, vision system, strategy receiver and transmitter, sensors, and coordination system. All these frameworks needed to be integrated to simplify the command of creating the complexity of the robot behaviors. To overcome these problems, the Robot Operating System (ROS) can be implemented on each robot. This paper presented the implementation of the ROS: Kinetic Kame in order to integrated the whole framework which is existed in the robot. To verify the performance of this system, some experiments has been done in real-time application. From the experimental results, the ROS: Kinetic Kame able to integrate each software framework of the robot in very good response.